Reduced beta cell function in offspring of mothers with young-onset type 2 diabetes. - Singh, R; Pearson, E; Avery, P; McCarthy, M; Levy, J; Hitman, G; Sampson, M; Walker, M; Hattersley, A (2006)
AIMS/HYPOTHESIS: Animal models indicate that even exposure to mild maternal hyperglycaemia in utero is detrimental to the beta cell function of the offspring, but evidence of this in humans is limited. In Europids who are diagnosed with type 2 diabetes before the age of 50 years, the risk of diabetes in the offspring of the diabetic mothers is greatly increased compared with the risk in those born to diabetic fathers. We hypothesised that offspring born to mothers with young-onset type 2 diabetes would have been exposed to mild hyperglycaemia in utero, so we studied the impact of this on their beta cell function. SUBJECTS AND METHODS: We measured beta cell function using early insulin response (EIR) after oral glucose; insulin resistance using HOMA; and HbA(1c) in 568 non-diabetic adult offspring born to parents with type 2 diabetes (mean age 55.8 years), split according to which parent was affected (in 327 it was the mother) and parental age of diagnosis: <50 years (n=117) or > or =50 years. To reduce the impact of genetic susceptibility, the offspring of affected fathers were used as control subjects. RESULTS: Offspring of mothers with young-onset type 2 diabetes had lower EIR (log EIR 4.32, 95% CI [4.14-4.51] vs 4.63 [4.43-4.83] p=0.02) and higher HbA(1c) (4.89% [4.79-4.99] vs 4.68% [4.57-4.79] p=0.02) than the offspring of fathers with young-onset type 2 diabetes. Insulin sensitivity was similar in the two groups. There were no differences in EIR or HbA(1c) between the offspring born to mothers and fathers who were diagnosed after the age of 50 years. CONCLUSIONS/INTERPRETATION: We conclude that the offspring of mothers with young-onset type 2 diabetes have a reduction in beta cell function. This is consistent with exposure to mild maternal hyperglycaemia programming beta cell function.